2012
DOI: 10.1029/2011gl050534
|View full text |Cite
|
Sign up to set email alerts
|

Vertical propagation of lakewide internal waves

Abstract: [1] Internal waves with diurnal period dominated velocities measured by an Acoustic Doppler Profiler (ADP) in a small lake (main basin 3000 m by 400 m by 18 m). ADP profiles and an along-lake temperature section indicate that the observed waves, like seiches, had horizontal wavelengths exceeding the metalimnion length. However, unlike non-dissipative seiches, the observed waves propagated vertically, carrying energy to the lakebed where waves were absorbed, rather than being strongly reflected. This absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 33 publications
7
30
0
Order By: Relevance
“…Since wave periods were comparable to the inertial period (17 h), theory suggests that along‐lake flows persisted sufficiently long to be deflected toward the across‐lake direction by Coriolis. Previously, for locations above the BBL, Henderson and Deemer [] found that substantial flow deflection was prevented by across‐lake tilting of isotherms and resulting baroclinic pressure gradients. Next, for locations within the BBL, it will be shown that major deflection was likely also prevented by baroclinic pressure gradients.…”
Section: Overview Of Observationsmentioning
confidence: 97%
See 4 more Smart Citations
“…Since wave periods were comparable to the inertial period (17 h), theory suggests that along‐lake flows persisted sufficiently long to be deflected toward the across‐lake direction by Coriolis. Previously, for locations above the BBL, Henderson and Deemer [] found that substantial flow deflection was prevented by across‐lake tilting of isotherms and resulting baroclinic pressure gradients. Next, for locations within the BBL, it will be shown that major deflection was likely also prevented by baroclinic pressure gradients.…”
Section: Overview Of Observationsmentioning
confidence: 97%
“…Velocities in this lake are dominated by fluctuations of a few cm/s, with periods in the range 0.4–1 day. These fluctuations result from a vertically propagating internal seiche, with upward phase propagation, horizontal wavelength about twice the lake length, and vertical wavelength less than the lake depth [ Henderson and Deemer , ]. Outside the BBL, velocities were predominantly directed along the long axis of the narrow lake.…”
Section: Field Site and Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations